2020
DOI: 10.3390/diagnostics10100762
|View full text |Cite
|
Sign up to set email alerts
|

PRINS lncRNA Is a New Biomarker Candidate for HPV Infection and Prognosis of Head and Neck Squamous Cell Carcinomas

Abstract: Numerous studies have shown that human papillomavirus (HPV) infection is one of the important risk factors for head and neck squamous cell carcinoma (HNSCC) progression and affects the expression of multiple genes, which might serve as new biomarkers. This study examines the effects of HPV infection on long non-coding RNA (lncRNA) expression and the immune system, particularly PRINS (Psoriasis susceptibility-related RNA Gene Induced by Stress). The Cancer Genome Atlas (TCGA) expression data for lncRNA genes an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 45 publications
(57 reference statements)
1
25
0
Order By: Relevance
“…However, the function of different lincRNAs is not fully understood. In the case of lncRNAs, our results indicated the role of lncRNA EGOT, PRINS, and CDKN2B-AS1 (ANRIL) [164,165]. Moreover, in our published work, we observed changes in lincRNAs including up-regulation of TTTY14, and TTTY15, and down-regulation of MEG3 and H19 in HPV(+) patients in comparison to HPV(−).…”
Section: Lincrnas In Hpv-positive Hnsccsupporting
confidence: 66%
See 1 more Smart Citation
“…However, the function of different lincRNAs is not fully understood. In the case of lncRNAs, our results indicated the role of lncRNA EGOT, PRINS, and CDKN2B-AS1 (ANRIL) [164,165]. Moreover, in our published work, we observed changes in lincRNAs including up-regulation of TTTY14, and TTTY15, and down-regulation of MEG3 and H19 in HPV(+) patients in comparison to HPV(−).…”
Section: Lincrnas In Hpv-positive Hnsccsupporting
confidence: 66%
“…We also observed that TTY14, TTY15, and MEG3 showed the high discrimination potential of HPV(−) and HPV(+) patients. However, no differences in the case of MALAT1 and CYTOR (LINC00152) depending on the HPV status based on TCGA data were noticed [165]. Tomar et al study based on HNSCC samples indicated changes of TTTY14, TTTY15, XIST, and CYTOR (LINC00152) depending on the HPV infection and activity status [166].…”
Section: Lincrnas In Hpv-positive Hnsccmentioning
confidence: 96%
“…These findings were consistent with our understanding that the three lncRNAs were associated with the prognosis of cancer. Moreover, previous study suggested that TTTY15 was associated with HPV infection, and which was upregulated in HPV-positive patients ( 41 ). Previous studies reported that Beclin 1 (BECN1) and LC3 are unique autophagy-related protein ( 42 ).…”
Section: Discussionmentioning
confidence: 94%
“…of note, abnormal lncrnas have been reported to be associated with HPV infection in cancers, including cc. For instance, lncrna psoriasis-susceptibility-related rna gene induced by stress (PrinS) has been indicated to be markedly higher in HPV+ patients with head and neck squamous cell carcinoma (HnScc) than that in HPV-patients with HnScc, and the expression of PrinS was significantly related to HPV-infected HnScc (25). Zhou et al (26) reported that lncrna oncogene-induced senescence 1 (lncrna-oiS1) is decreased in HPV+ patients with cervical squamous cell carcinoma (cScc) and HPV+ Hr, hazard ratio; HPV, human papillomavirus; BMi, body mass index; FiGo, international Federation of Gynecology and obstetrics; dleu1, long noncoding rna deleted in lymphocytic leukemia 1. cScc cells and may enhance the proliferation of HPV+ cScc cells.…”
Section: Discussionmentioning
confidence: 99%